Ionic Liquids Synthesis – Methodologies - Ferraz, Ricardo (2021)
Ionic Liquids (IL) are salts with at least one organic cation. The term “Ionic Liquid” has been restricted to salts with melting point below 100° C [1]. In the recent years, (ILs) have gained popularity in science and technology. The large number of possible cation/ anion combinations allows a great variety of tunable interactions; also their unique properties and characteristics make it a promising and an attractive to work with in several fields. However, how ILs are produced? This editorial pretends to make a brief commentary of some of the main methodologies of ILs synthesis